Long Non-coding RNA RP11-480I12.5 Promotes the Proliferation, Migration, and Invasion of Breast Cancer Cells Through the miR-490-3p-AURKA-Wnt/β-Catenin Axis - Gao, Xinya; Lai, Yuanhui; Zhang, Zhanqiang; Ma, Yanfei; Luo, Zhizhai; Li, Yanghong; Yang, Ciqiu; Lu, Guanming; Li, Jie (Frontiers in Oncology, 2020)
Background: RP11-480I12.5 is a newly identified long noncoding RNA (lncRNA) that has never been studied in breast cancer. The biological function of RP11-480I12.5 in breast carcinoma and its underlying mechanism are still unknown. Methods: We scanned the Cancer Genome Atlas (TCGA) database and identified RP11-480I12.5 as one of the most dysregulated lncRNAs. The level of RP11-480I12.5 was assessed in breast cancer (BC) tissue samples and BC cell lines. The prognostic value of RP11-480I12.5 expression was assessed using the Kaplan-Meier method. The biological influence of RP11-480I12.5 on BC cell lines was studied using proliferation, Transwell migration, and invasion assays. Results: RP11-480I12.5 was upregulated in both the TCGA database and our own database. Moreover, Kaplan-Meier and Cox proportional hazards analyses indicated that high RP11-480I12.5 expression was related to poor overall survival. Moreover, RP11-480I12.5 promotes the proliferation, migration and invasion of BC. RP11-480I12.5 promotes the expression of AURKA and the downstream Wnt/β-catenin pathway by sponging miRNA miR-490-3p. Conclusion: Taken together, our results indicate that RP11-480I12.5 is associated with tumour progression in breast cancers. Our findings indicate that the long noncoding RNA RP11-480I12.5 promotes the proliferation, migration and invasion of breast cancer cells through the miR-490-3p-AURKA-Wnt/β-catenin axis, which may serve as a therapeutic target in the future.